Prosumption: as novas articulações entre trabalho e consumo na reorganização do capital - Isleide Arruda Fontenelle (Ciências Sociais Unisinos)
The article analyzes the phenomenon of prosumption on the basis of the re-significations that the term underwent in the context of the restructuring of production in the 1980s and the new links between work and consumption resulting from that. Based on academic texts and empirical illustrations, as well as on Marxian literature on the production of value, the aim of the paper is to understand how the formatting of the consumer-worker and worker-consumer takes place and to discuss the way in which contemporary capital has sought to deal with two of its main challenges: the extension of abstract labor and the overcoming of the temporal gap between production and realization of value. This process points to novel and more subtle forms of exploitation of the worker and the consumer and requires a return to Marx to think about the blurred boundaries between production and realization of value in these new forms of work and consumption.